2006
DOI: 10.1002/bit.20766
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen supply for CHO cells immobilized on a packed-bed of Fibra-Cel® disks

Abstract: Packed-bed bioreactors (PBR) have proven to be efficient systems to culture mammalian cells at very high cell density in perfusion mode, thus leading to very high volumetric productivity. However, the immobilized cells must be continuously supplied with all nutrients in sufficient quantities to remain viable and productive over the full duration of the perfusion culture. Among all nutrients, oxygen is the most critical since it is present at very low concentration due to its low solubility in cell culture medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…All animal cell cultures are aerobic processes in which the oxygen requirement varies between cell lines. The effects of oxygen concentration on animal cell cultures have been studied by many authors (26)(27)(28)(29)(30). Link et al reported that a dissolved oxygen concentration of 5% resulted in the lowest viable cell density and product concentration, likely due to oxygen limitation in the batch culture of CHO-K1 cell line (31).…”
Section: Detrimental Effects Of Acidic and Hypoxic Conditions On Rchomentioning
confidence: 98%
“…All animal cell cultures are aerobic processes in which the oxygen requirement varies between cell lines. The effects of oxygen concentration on animal cell cultures have been studied by many authors (26)(27)(28)(29)(30). Link et al reported that a dissolved oxygen concentration of 5% resulted in the lowest viable cell density and product concentration, likely due to oxygen limitation in the batch culture of CHO-K1 cell line (31).…”
Section: Detrimental Effects Of Acidic and Hypoxic Conditions On Rchomentioning
confidence: 98%
“…Thus, the micro-bioreactor should be operated at Re above 500. However, to have an optimal concentration around 50% of saturation [37], the Reynolds number should be around 1000. to bottom surfaces. At a Re from 1000 to 2000, the minimum location moves towards the left edge.…”
Section: Oxygen Concentrationmentioning
confidence: 99%
“…In fixed bed bioreactors cells are immobilized on or encapsulated in a stationary matrix consisting of particles densely packed in a cylindrical vessel. Several types of particles have been used to date: Macro-porous microcarriers, porous ceramic beads, porous glass beads, glass fibers, polyester discs, alginate beads and hydrogels [62,[231][232][233][234][235][236]. The culture medium is perfused through the bed of the bioreactor and supplies cells with nutrients while removing undesired metabolites.…”
Section: Single-use Versions Of Fixed Bed Bioreactors and Msc Expansionsmentioning
confidence: 99%